Interreligious Dialogue for Peacebuilding: A Hermeneutical-philosophical Approach to the Ethics of Understanding in a Post-Conflict Africa - (:unkn) unknown (My University, 2025)
This article examines the ethical and philosophical foundations of interreligious dialogue as a transformative pathway for sustainable peacebuilding in post-conflict African contexts. It situates the conversation within a hermeneutical-philosophical framework, drawing principally on the dialogical ethics of Hans-Georg Gadamer and indigenous African moral traditions. The central objective is to investigate how an ethics of understanding—grounded in mutual recognition, narrative, and historical memory—can serve not only as a practical tool for reconciliation but also as a fundamental philosophical reorientation toward human dignity, pluralism, and coexistence. The research addresses a critical problem facing many African societies emerging from conflict: the instrumentalization of religion in political violence and its lingering effects on intercommunal trust and social cohesion. Despite various peace accords and transitional justice mechanisms, the ethical dimension of dialogue—particularly the deep listening and interpretive engagement required for genuine understanding—remains underdeveloped. This gap is especially pronounced in settings where religious diversity intersects with colonial legacies, ethnic tensions, and epistemic injustice. The study therefore asks: What philosophical resources can be mobilized to reframe interreligious dialogue as a process of healing and ethical transformation, rather than mere political utility? Methodologically, the article adopts a qualitative, interdisciplinary approach grounded in philosophical hermeneutics. It engages in critical textual analysis of key philosophical texts—especially Gadamer’s Truth and Method—and African communitarian ethics from thinkers such as John Mbiti, Kwasi Wiredu, and Mogobe Ramose. It also incorporates case illustrations from select post-conflict African regions (e.g., Rwanda, South Sudan, and northern Nigeria) to contextualize the ethical claims within lived realities. T
Keywords: African Research